CircRNA-mediated regulation of brown adipose tissue adipogenesis - Liu, Kaiqing; Liu, Xin; Deng, Yaqin; Li, Zesong; Tang, Aifa (Frontiers in Nutrition, 2022)
Adipose tissue represents a candidate target for the treatment of metabolic illnesses, such as obesity. Brown adipose tissue (BAT), an important heat source within the body, promotes metabolic health through fat consumption. Therefore, the induction of white fat browning may improve lipid metabolism. Currently, the specific roles of circRNA in BAT and WAT remain elusive. Herein, we conducted circRNA expression profiling of mouse BAT and WAT using RNA-seq. We identified a total of 12,183 circRNAs, including 165 upregulated and 79 downregulated circRNAs between BAT and WAT. Differentially expressed (DE) circRNAs were associated with the mitochondrion, mitochondrial part, mitochondrial inner membrane, mitochondrial envelope, therefore, these circRNAs may affect the thermogenesis and lipid metabolism of BAT. Moreover, DE circRNAs were enriched in browning- and thermogenesis-related pathways, including AMPK and HIF-1 signaling. In addition, a novel circRNA, circOgdh, was found to be highly expressed in BAT, formed by back-splicing of the third and fourth exons of the Ogdh gene, and exhibited higher stability than linear Ogdh. circOgdh was mainly distributed in the cytoplasm and could sponge miR-34a-5p, upregulating the expression of Atgl, a key lipolysis gene, which enhanced brown adipocyte lipolysis and suppressed lipid droplet accumulation. Our findings offer in-depth knowledge of the modulatory functions of circRNAs in BAT adipogenesis.